Analysis of slope failure at km 43.2 route c130 Kuala Wau-Kertau road using slope - Muhammad Hafiz, Ishak (2009)
Slope stability issues become one of the main problems in construction industry due to nature of the topography and the weather conditions in Malaysia. Improper slope analysis design might cause slope failure which has been acknowledged as one of the most frequent disaster that can lead to great loss of properties and life. To overcome this problem, analysis of slope failure must be carried out to determine the slope stability. This slope failure study has contributed to local engineering studies regarding the slope failure that occurred at Kuala Wau-Kertau road which located in Maran. This study analyses the slope stability and proposes the method of ground improvement to be applied on the slope in term of factor of safety (FOS) and cost. Data from the soil investigation report of the slope is used to analyze the stability of the slope using GeoStudio 2007 Slope/w. From the results, the FOS of the slope before the failure by using Morgenstern-Price Method is 1.710 which can be considered as stable due to the FOS value is more than 1. According to FOS value, the failure is not due to improper design at the preliminary stages of constructing the road but may be due to other factors. By comparing the analysis of remedial measures to the slope, the best method remedial measure to be applied on the slope in term of FOS value and cost is by using anchors. The FOS value of the slope after applying anchors on the slope increased to 2.370. The overall estimated cost of applying this method on the slope is about RM 500,000. The results that have been determined from this study can be made as reference for engineers in order to improve the slope stability of Kuala Wau-Kertau road or any other slope in the future.